The mechanism(s) and management of dicamba resistance in kochia (Kochia scoparia) - Ou, Junjun (Kansas State University, 2018)
Kochia (Kochia scoparia (L.) Schrad), one of the most troublesome weeds in the North American Great Plains, including Kansas (KS), has become a significant concern in croplands ever since the evolution and spread of glyphosate resistance in this weed. Dicamba, an important synthetic auxin herbicide, is a useful substitute for managing glyphosate-resistant (GR) broadleaf weeds. As a result of extensive and intensive use, kochia populations have also developed resistance to dicamba. However, the precise mechanism(s) of dicamba resistance in kochia is still unknown. In the first part of this dissertation, the physiological, biochemical and genetic basis of dicamba resistance in dicamba-resistant (DR) kochia from KS was investigated. The results suggest that the mechanism of dicamba resistance in this kochia is not due to decreased absorption, reduced translocation or enhanced detoxification of dicamba. In contrary, reduced translocation of dicamba was found to contribute to the dicamba resistance in DR kochia from Colorado (CO). Further investigation of DR kochia from KS revealed a possible role of single nucleotide polymorphism (SNP) in TIR1 (the receptor gene of auxin) in the dicamba resistance evolution. Genetic analyses of data from inheritance studies demonstrated that an incomplete dominant nuclear gene controls the dicamba resistance in kochia from KS. Also, it was found that the genes controlling dicamba resistance in kochia from KS and CO are not linked. Similarly, although, GR and DR traits were found to be controlled by two distinct single dominant genes, they appear to co-exist in many kochia populations from KS. Nonetheless, these two genes were also found not to be linked. The second part of this dissertation focused on the development of reliable tools for the management of DR and/or GR kochia. The following experiments were conducted under greenhouse and field conditions in KS: a) the effect of temperature stress on the efficacy of dicamba or glyphosate; b) efficacy of dicamba and glyphosate when applied in combination; and c) efficacy of dicamba when used as pre-emergence (PRE) herbicide. The results suggest that the efficacy of both dicamba and glyphosate on kochia can be improved when applied at cooler temperature conditions. Also, it was found that the dicamba and glyphosate tank-mix should not be recommended to manage kochia, especially DR kochia, due to significant antagonistic interaction when applied in combination. On the other hand, application of dicamba as PRE compared to the postemergence application, was found to improve kochia control including DR kochia. Overall, this dissertation provided several novel outcomes both in basic and applied aspects of dicamba resistance in kochia.
Keywords: Kochia scoparia; dicamba; resistance; mechanism; management